2007
DOI: 10.1007/s10529-007-9520-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production in anaerobic and microaerobic Thermotoga neapolitana

Abstract: We have tested the hypothesis (Van Ooteghem et al. Appl Biochem Biotechnol 2002 98-100: 177-189) that microaerobic metabolism may increase the yield of H(2) from the thermophilic bacterium Thermotoga neapolitana. In anaerobic conditions, T. neapolitana converted glucose into acetic acid and lactic acid and yielded 2.4 +/- 0.3 mol H(2) mol(-1) glucose. The bacterium tolerated low O(2) partial pressures but the H(2) yield was not improved under microaerobic conditions. Our results indicate that T. neapolitana on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 19 publications
5
33
0
Order By: Relevance
“…Microaerobic species, that require O 2 partial pressures below atmospheric levels for aerobic metabolism, have been described such as Klebisalle oxytoca HP1. 24 The question of oxygen tolerance and potential microaerobic metabolism of T. neapolitana and T. maritima has been raised in several studies 10,12,14,22,25,26 and is addressed here. Belkin et al 10 and Childers et al 22 found that it was possible to maintain cultures under aerobic conditions at temperatures below the temperature range for growth.…”
Section: V C 2009 American Institute Of Chemical Engineersmentioning
confidence: 98%
See 1 more Smart Citation
“…Microaerobic species, that require O 2 partial pressures below atmospheric levels for aerobic metabolism, have been described such as Klebisalle oxytoca HP1. 24 The question of oxygen tolerance and potential microaerobic metabolism of T. neapolitana and T. maritima has been raised in several studies 10,12,14,22,25,26 and is addressed here. Belkin et al 10 and Childers et al 22 found that it was possible to maintain cultures under aerobic conditions at temperatures below the temperature range for growth.…”
Section: V C 2009 American Institute Of Chemical Engineersmentioning
confidence: 98%
“…9 T. neapolitana is a rod-shaped, gram-negative bacterium that grows between 55 and 90 C. 10,11 T. neapolitana consumes a variety of carbohydrate substrates including ribose, xylose, glucose, sucrose, maltose, lactose, galactose, starch, and glycogen. 11 Although some of the metabolic products of T. neapolitana have been analyzed, [12][13][14][15] complete carbon and electron equivalents balances are not currently available for this species and are presented here. Such data is available for the related organism Thermotaga Correspondence concerning this article should be addressed to L. P. Walker at lpw1@cornell.edu.…”
Section: Introductionmentioning
confidence: 99%
“…As noted previously in various other studies [19], yields under thermophilic conditions tend to be higher. Thus, a thermophilic bacterium, Thermotoga neapolitana, gave a hydrogen yield of 2.4 ± 0.3 mol H 2 mol -1 glucose with acetic acid and lactic acid as additional metabolic end products [61]. For reasons that aren't clear, malonic acid addition increased H 2 yields to 3.5-3.8 mol H 2 mol -1 glucose.…”
Section: Isolation and Properties Of Novel Hydrogen Producersmentioning
confidence: 98%
“…Thermotoga neopolitana was first described by Jannasch and co-workers (1988) but earliest data of H 2 production is from 2002 where the bacterium produced 2.0 ml L -1 h -1 on glucose in batch cultures (van Ootegehem et al, 2002). H 2 production capacity from glucose by this species has since then been investigated in detail by others (Eriksen et al, 2008 (van Niel et al, 2002) and T. maritima (Nguyen et al, 2008;Schröder et al, 1994) with H 2 yields varying from 1.67 to 4.00 (maximum) mol H 2 mol glucose -1 . Table 3.…”
Section: Wwwintechopencommentioning
confidence: 98%